Awareness of Philosophical Issues among Fifth-grade Literary Female Students - Abdulhadi, Zahraa Muqdad; Khamees, Tariq Hashim (Journal of Tikrit University for Humanities, 2025)
This study aimed to investigate the level of awareness of philosophical issues among female fifth-grade literary students in the preparatory and secondary schools of Salah Al-Din Governorate. The study population consisted of female fifth-grade literary students in Tikrit Education Department who were studying philosophy and psychology in the second semester of the 2023-2024 academic year. The researchers randomly selected female fifth-grade literary students from Al-Baroudi High School and Al-Khansa High School for Girls to form the research sample. The researchers employed two research methodologies: the descriptive method and the quasi-experimental method. The descriptive method was used to identify the philosophical issues, determine the students' level of awareness, and develop measurement procedures. The quasi-experimental method was used to test the study's hypotheses. To achieve the study's objectives, the researchers developed a list of philosophical issues suitable for the sample's intellectual level and constructed a philosophical awareness test consisting of 7 issues, each with three alternatives. After administering the test to the students in the research sample and statistically analyzing the data, the study's results showed that the students exhibited a high level of awareness of philosophical issues. In the conclusion of the study, the researchers arrived at a set of findings, conclusions, recommendations, and suggestions.